2014
DOI: 10.1089/jpm.2013.0157
|View full text |Cite
|
Sign up to set email alerts
|

Volunteers in Specialist Palliative Care: A Survey of Adult Services in the United Kingdom

Abstract: Background: Worldwide, the demand for specialist palliative care is increasing but funding is limited. The role of volunteers is underresearched, although their contribution reduces costs significantly. Understanding what volunteers do is vital to ensure services develop appropriately to meet the challenges faced by providers of palliative care. Objective: The study's objective is to describe current involvement of volunteers with direct patient/family contact in U.K. specialist palliative care. Design: An onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 13 publications
1
60
0
Order By: Relevance
“…Characteristics of the eight included studies are detailed in Table 2. In our UK-wide survey on the role of volunteers in palliative care, survey respondents did not provide us information on any other evaluations on the impact of volunteers (Burbeck et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the eight included studies are detailed in Table 2. In our UK-wide survey on the role of volunteers in palliative care, survey respondents did not provide us information on any other evaluations on the impact of volunteers (Burbeck et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…We contacted researchers in the field for unpublished studies. As part of a parallel research project, which was a national UK survey on the role of volunteers in palliative care (Burbeck et al, 2014), we asked managers of volunteers for copies of any in-house research on the impact of volunteers.…”
Section: Search Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Trained volunteers are an important and cost-effective component of bereavement care service provision in many palliative care services. 15,16 However, we know little about how the volunteers are trained or supervised. 17 One study showed that although the majority of palliative care volunteers providing bereavement support had personal experience of bereavement and were provided with some generic training on the volunteer role, only a third received training in bereavement support.…”
mentioning
confidence: 99%
“…We have carried out a similar survey of adult services17 but no other similar survey of adult services has been undertaken. We found that the number of volunteers in children's services with direct contact with children, young people and their families is small (median 25 per service (IQR 11–70)) compared with those in adult services (median 85 per service IQR 40–150) (ref.…”
Section: Discussionmentioning
confidence: 99%